2007
DOI: 10.1590/s0100-204x2007000300009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of ninety elite soybean cultivars using coefficient of parentage

Abstract: -The objective of this work was to estimate the coefficient of parentage and to understand the genetic structure of 90 elite soybean cultivars, which are adapted to different Brazilian environments. A total of 4,005 coefficients of parentage (f) were obtained and used to group the cultivars by UPGMA method. The constructed dendrogram showed several related cultivar groups which shared similar ancestors and clearly showed the genetic structure of the main Brazilian cultivars. Effective population sizes (Ne) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
5

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 4 publications
(4 reference statements)
1
20
0
5
Order By: Relevance
“…Despite the high number, the Brazilian soybean cultivars are extremely uniforms because they originated from only a few ancestral lines, which resulted in a narrow genetic base of germplasm (Miranda et al, 2007;Priolli et al, 2010;Wysmierski and Vello, 2013). This fact, together with the lack of genetic variability, brings risks for cultivars productivity levels and susceptibility to pests, pathogens and environmental stresses.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the high number, the Brazilian soybean cultivars are extremely uniforms because they originated from only a few ancestral lines, which resulted in a narrow genetic base of germplasm (Miranda et al, 2007;Priolli et al, 2010;Wysmierski and Vello, 2013). This fact, together with the lack of genetic variability, brings risks for cultivars productivity levels and susceptibility to pests, pathogens and environmental stresses.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…The cultivars CD243 and BRS Juliana formed the isolated groups V and VII, respectively. Miranda et al (2007) studying the genetic structure of 90 elite soybean cultivars adapted to different Brazilian environments, have concluded that the UPGMA method was efficient for clustering the cultivars in several groups, according to their common ancestral. Moreover, this method was also efficient to demonstrate the genetic structure of the main Brazilian cultivars.…”
Section: Group Rr Soybean Cultivarsmentioning
confidence: 99%
“…The Brazilian soybean cultivars have great diversity in canopy characteristics such as plant size, architecture, branch and raceme level, and leafiness of plants (Priolli et al, 2002;Oliveira et al, 2003;Miranda et al, 2007;Mulato et al, 2010, Oliveira et al, 2012. These characteristics are genetic base dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Faria et al (2007) o progresso genético direcionado em qualquer espécie está relacionado à existência de variabilidade genética. A soja é uma cultura que, pelos estudos de grau de parentesco e divergência genética, apresenta alta similaridade entre os cultivares desenvolvidos (BONATO et al, 2006;HYTEN et al, 2006;MIRANDA et al, 2007;WYSMIERSKI;VELLO, 2013).…”
Section: Introductionunclassified